Optical absorption, photocarrier recombination dynamics and terahertz dielectric properties of electron-irradiated GaSe crystals - Bereznaya, Svetlana A.; Redkin, Ruslan A.; Brudnyi, Valentin N.; Sarkisov, Yuri S.; Su, Xinyang; Sarkisov, Sergey Yu (Crystals)
Optical absorption spectra of 9 MeV electron-irradiated GaSe crystals were studied. Two absorption bands with the low-photon-energy threshold at 1.35 and 1.73 eV (T = 300 K) appeared in the transparency region of GaSe after the high-energy-electron irradiation. The observed absorption bands were attributed to the defect states induced by Ga vacancies in two charge states, having the energy positions at 0.23 and 0.61 eV above the valence band maximum at T = 300 K. The optical pump-terahertz probe technique (OPTP) was employed to study the dark and photoexcited terahertz conductivity and charge carrier recombination dynamics at two-photon excitation of as-grown and 9 MeV electron-irradiated GaSe crystals. The measured values of the differential terahertz transmission at a specified photoexcitation condition were used to extract the terahertz charge carrier mobilities. The determined terahertz charge carrier mobility values were ~46 cm2/V·s and ~14 cm2/V·s for as-grown and heavily electron-irradiated GaSe crystals, respectively. These are quite close to the values determined from the Lorentz-Drude-Smith fitting of the measured dielectric constant spectra. The photo-injection-level-dependent charge carrier lifetimes were determined from the measured OPTP data, bearing in mind the model injection-level dependencies of the recombination rates governed by interband and trap-assisted Auger recombination, bulk and surface Shockley-Read-Hall (SRH) recombination and interband radiative transitions in the limit of a high injection level. It was found that GaSe possesses a long charge carrier lifetime (a~1.9×10−6 ps−1, b~2.7×10−21 cm3ps−1 and c~1.3×10−37 cm6ps−1), i.e., τ~0.53 μs in the limit of a relatively low injection, when the contribution from SRH recombination is dominant. The electron irradiation of as-grown GaSe crystals reduced the charge carrier lifetime at a high injection level due to Auger recombination through radiation-induced defects. It was found that the terahertz spectra of the dielectric constants of as-grown and electron-irradiated GaSe crystals can be fitted with acceptable accuracy using the Lorentz model with the Drude-Smith term accounting for the free-carrier conductivity.